Ценотична різноманітність ковилових степів басейну р. Базавлук - Kucherevskyi, V.V.; Provozhenko, T.A.; Sirenko, T.V. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2009)
It is studied cenotic variety of feather-grasses steppes in a river basin of Bazavluk, developed them ecologycal and cenotic classification. As a result of geobotanical descriptions 7 basic structures and 21 associations are selected.